Banking industry response to competition from the financial inclusion paradigm in Africa - Kamau, Simon Muhia (University of the Witwatersrand, Johannesburg, 2021)
This study examines the effects of increased competition from microfinance institutions (MFIs)– reflective of the financial inclusion paradigm – on commercial banks in Africa. More specifically, I analyze the banking industry’s response to competition for financial inclusion and how the response affects the cost efficiency, asset portfolio risk, and social outreach (performance) of the banking industry. I employ panel data comprising 16 countries that possess the most advanced national banking markets in Africa, for the period 2010-2017. Fixed effects model (FE), Fractional Probit regression method (FRM), and Generalized methods of moments (GMM) are variously the main estimation techniques. I find that banks are responding to the competition for financial inclusion by increasing the supply of credit to households and SMEs, in support of the market power hypothesis of competition. Furthermore, estimation results show strong evidence that increased supply of credits to households and SMEs, in response to competition for financial inclusion, contributes positively to the banking industry’s cost-efficiency. Additionally, results suggest that increased bank lending to households and SMEs has a negative but statistically insignificant effect on banking stability. Interestingly, additional results indicate that banks’ positive response to the financial inclusion paradigm is mainly limited to the relatively wealthier segment of the low-income population. Moreover, these findings are robust to using alternative measures of competition for financial inclusion, and banking industry response, among several other robustness checks. From these results and more, I recommend policies such as enabling access to borrowers' information and supporting the development of financial market infrastructure, in order to promote competition in providing financial services to the low-income market and further drive financial inclusion. I also recommend the adoption of improved and proactive regulatory measures to ensure that competition for financial inclusion does not compromise the stability of the banking industry. Lastly, I propose policies that would ensure that competition for financial inclusion does not hurt outreach to the poorest segment of the population, as banks seek to enhance their efficiency while providing financial services to households and SMEs
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Finance to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Competition for financial inclusion; Microfinance institutions; Banking industry response; Cost efficiency; Portfolio risk; Banking outreach; Africa; UCTD; SDG-8: Decent work and economic growth